2010
DOI: 10.1029/2009gb003749
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur deposition causes a large‐scale growth decline in boreal forests in Eurasia

Abstract: [1] Human activity has altered climate, atmospheric carbon dioxide concentrations, and the concentrations of several pollutants over the last few decades. At the same time, short-term reactions of tree growth to climatic variations have changed during the last few decades, for reasons that are poorly understood. However, the effects of the pollutants on growth of boreal forests in these remote areas have not been quantified, but even small changes in the productivity of boreal forest should have a large effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 82 publications
0
9
0
2
Order By: Relevance
“…The growth and life cycles of herbivores or their habitat conditions may change in such a way that the outbreak frequencies and intensities of previously relatively harmless herbivore populations increase (Hunter et al, 2014). At the same time as climate is changing, boreal vegetation is also exposed to increased anthropogenic influences by pollutant deposition and land use changes (Dentener et al, 2006;Bobbink et al, 2010;Savva and Berninger, 2010). Large industrial complexes may lead to local forest diebacks, as has been observed in the Kola region (e.g.…”
Section: Ecosystem Structural Changes and Resiliencementioning
confidence: 98%
“…The growth and life cycles of herbivores or their habitat conditions may change in such a way that the outbreak frequencies and intensities of previously relatively harmless herbivore populations increase (Hunter et al, 2014). At the same time as climate is changing, boreal vegetation is also exposed to increased anthropogenic influences by pollutant deposition and land use changes (Dentener et al, 2006;Bobbink et al, 2010;Savva and Berninger, 2010). Large industrial complexes may lead to local forest diebacks, as has been observed in the Kola region (e.g.…”
Section: Ecosystem Structural Changes and Resiliencementioning
confidence: 98%
“…Everything else being equal, these additional N inputs into ecosystems can potentially lead to an increased carbon sink (Reay et al 2008). Sulfate deposition, on the other hand, has been linked to a decrease in tree growth as a result of acidification (Savva and Berninger 2010). We focus here on the analysis on land.…”
Section: Nitrogen and Sulfate Depositionmentioning
confidence: 99%
“…Speer et al 2001;Veblen et al 1991), forest fires (Swetnam 1993), snow avalanches (Veblen et al 1994), flooding (Yanosky and Jarrett 2002), forest stand dynamics (Fraver et al 2009), environmental pollution (e.g. Elling et al 2009;Rydval and Wilson 2012;Savva and Berninger 2010;Wilson and Elling 2004), timber harvesting, and woodland clearance (Bebber et al 2004;Nowacki and Abrams 1997). A common approach to disturbance detection is based on the statistical identification of disturbance events manifested as either growth suppression or releases in the RW record with duration of one or more years to several decades.…”
Section: Detecting Disturbancementioning
confidence: 99%